Implementasi Perlindungan Hukum terhadap Penyampaian Keluhan Layanan Kesehatan Rumah Sakit oleh Pasien dengan Media Massa - Lusiana Apriliyanti; Dwi Cornelita Anggraini; Nena Ayu Sabrina; Destyan Wahyu Ningtyas; Muhammad Aufa Kamal (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Issues related to patients who complain about health services in hospitals with the mass media are important and complex issues. Patients have the right to complain about the services received, and hospitals have the obligation to follow up on these complaints. However, in practice, there are still several obstacles that hinder the implementation of legal protection. These obstacles include patients' lack of understanding of their rights, limited access for patients to submit complaints, imbalance in legal protection for patients and hospitals, and unbalanced media coverage. To overcome these obstacles, concrete efforts are needed from various stakeholders, such as increasing patient understanding, providing easily accessible means of complaints, and improving regulations related to health services in hospitals through the mass media. With the implementation of these suggestions, it is expected that legal protection for patients can be improved, and better health services can be realized.